Poly (ethylene-co-vinyl alcohol)-based polymeric thermo-responsive nanocarriers for controlled delivery of epirubicin to hepatocellular carcinoma - Farshid Hassanzadeh; Maryam Farzan; Jaleh Varshosaz; Ghadam Ali Khodarahmi; Sahar Maaleki; Mahboubeh Rostami (Wolters Kluwer Medknow Publications, 2017)
In this study, poly(ethylene-co-vinyl alcohol) (EVOH) as a novel biocompatible polymeric scaffold was surface modified by succinylation to get EVOHS and further pegylated to improve structural properties using methoxypolyethylene glycol (5000 Da) succinate (PEGS) along with targeting with retinoic acid (RA) to get final modified active and passive targeted conjugate (PEGS-EVOHS-RA) to evaluate its ability in carrying and delivery of epirubicin to hepatocellular carcinoma cell lines in response to varying temperatures. In this regard, the PEGS-EVOHS-RA conjugate was prepared through the desired chemical reactions and its structure was confirmed using 1H-NMR and FT-IR spectra. The micelles were prepared from PEGS-EVOHS-RA by dialysis method. The Particle size and zeta potential were measured, and entrapment efficacy along with in vitro release efficiency in different temperatures were also studied. The structural morphology of optimized nanomicelle was studied by transmission electron microscopy micrographs. The desired final micelles were evaluated for their toxicity using MTT assay on HepG2 human hepatocellular carcinoma cell lines at normal (37 °C) and elevated temperature (45 °C). The results revealed that, as the hydrophilicity of micelles increased, all characteristic properties improved. Then, these micelles can be considered as potentially effective thermo responsive delivery systems for targeted delivery of cytotoxic agents to hepatocellular carcinoma.